BUREAUCRACY CULTURE: PERFORMANCE OF SAMSAT MAROS EMPLOYEES IN MOTOR VEHICLE TAX PAYMENT SERVICES - Ahmad Rosandi Sakir; Rabinah Yunus; Suhardiman Syamsu (Jurnal Administrasi Negara, 2021)
Public service is a form of service provided by the bureaucracy/government to the community. The implementation of public services is intended to meet the needs in accordance with the wishes and expectations of the community. One of the sources of regional income comes from the Motor Vehicle Tax (PKB). Motor Vehicle Taxes have an important role in regional development, so it is only natural that every individual or community owner of motorized vehicles is obedient and punctual in paying taxes in accordance with the law in order to facilitate programs and activities that have been planned by the regional government. And the bureaucracy in terms of service should also be free from deviant things so that services can run well. The research method is qualitative deductive. Respondents are the head of the Maros Revenue Unit and the taxpayer community. The results of the study explain that several factors that cause the less than optimal motor vehicle tax revenue for the apparatus that are considered are still lacking in discipline. Some of the factors that cause employees are often late, rampant brokers, and rewards and punishments that don’t work well.